The Effectiveness of Understanding Islamic Values on Environmental Awareness and Behavior of Gen Z in Bandar Lampung - Mulyadi, Mulyadi; Jauhari, Tontowi; Al Fajar, Adam Hafidz (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to measure the effectiveness of understanding Islamic values in relation to the environmental awareness and behavior of Generation Z in Bandar Lampung. Values such as tauhid, khalifah, fitrah, and mizan are understood to play an important role in shaping ecological awareness. This research employs a quantitative approach with a correlation method. The study was conducted in Bandar Lampung with a population of Gen Z students (born 1997–2012). Primary data were collected using structured questionnaires. Purposive sampling was used to select 217 respondents based on criteria of age, location, and educational status. This sample is considered representative of analyzing the relationship between Islamic values and environmental awareness. Secondary data were obtained from literature and reports. For data analysis, the following steps were applied: 1) reliability testing using Cronbach's Alpha, 2) descriptive analysis, 3) Pearson correlation, and 4) multiple linear regression to examine the relationship between Islamic values, environmental awareness, and eco-friendly behavior. This study shows that understanding Islamic values has a strong relationship with environmental awareness (r = 0.861) and environmental care behavior (r = 0.546). Overall, these two variables explained 74.1% of the variance in environmental caring behavior, confirming the importance of Islamic education in raising ecological awareness.